2004
DOI: 10.1128/jcm.42.6.2752-2758.2004
|View full text |Cite
|
Sign up to set email alerts
|

Ileocolitis Associated with Anaerobiospirillum in Cats

Abstract: Ileocolitis associated with spiral bacteria identified as an Anaerobiospirillum sp. was found in six cats. Two cats had acute onset of gastrointestinal signs characterized by vomiting and diarrhea in one cat and vomiting in another cat, one cat had chronic diarrhea that was refractory to medical therapy; one cat had acute onset of anorexia and lethargy, and two cats had clinical signs that were not related to the gastrointestinal tract. The presence of an Anaerobiospirillum sp. was demonstrated on the basis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 27 publications
1
14
0
3
Order By: Relevance
“…Lean Ossabaw minipigs with lower fasting insulin levels (15 pmol/liter versus 34.7 pmol/liter) had a higher abundance of Bacteroidetes in colon than obese pigs (45). In the present study, a lower relative abundance of Proteobacteria was observed in the KF group, which can be considered beneficial, as increased Proteobacteria levels are linked with intestinal inflammation (46), and this phylum encompasses bacteria known to cause intestinal pathology in humans and animals (47,48). Interestingly, this reduction in Proteobacteria levels in the KF diet group was associated with a decrease in the plasma TNF-␣ concentration during lactation in the same sows.…”
Section: Discussionsupporting
confidence: 48%
“…Lean Ossabaw minipigs with lower fasting insulin levels (15 pmol/liter versus 34.7 pmol/liter) had a higher abundance of Bacteroidetes in colon than obese pigs (45). In the present study, a lower relative abundance of Proteobacteria was observed in the KF group, which can be considered beneficial, as increased Proteobacteria levels are linked with intestinal inflammation (46), and this phylum encompasses bacteria known to cause intestinal pathology in humans and animals (47,48). Interestingly, this reduction in Proteobacteria levels in the KF diet group was associated with a decrease in the plasma TNF-␣ concentration during lactation in the same sows.…”
Section: Discussionsupporting
confidence: 48%
“…A lower relative abundance of Proteobacteria was also observed at weaning for offspring of GM maize-fed sows, and this may have been due to the influence of the maternal microbiota; however, it was not associated with treatment differences in any member taxa. These reductions can be considered beneficial as increased Proteobacteria have been linked with intestinal inflammation (31), and this phylum encompasses bacteria known to cause intestinal pathology in humans and animals (32,33). Interestingly, this reduction in Proteobacteria was associated with beneficial immune effects in the same sows (34).…”
Section: Discussionmentioning
confidence: 99%
“…The likelihood of observing these microorganisms is enhanced by high-power examination of areas of the preparation that contain a lesser amount of background flora, such as very thin areas of the preparation or areas of the preparation that are mucus-rich because these microorganisms localize to the mucus-rich mucosal surface. Diarrhea has been associated with fecal isolation of bacteria from all of these genera except for the treponeme-like bacteria, and bacteria from all of these genera have also been isolated from the feces of asymptomatic dogs and cats (Bender et al, 2005;Broussard, 2003;De Cock et al, 2004;Malnick et al, 1990;Misawa et al, 2002;Rossi et al, 2008). Concurrent observation of fecal neutrophils would support a bacterial cause of the diarrhea.…”
Section: Potential Microbial Pathogensmentioning
confidence: 88%